Hepatic Gener expression in Solea senegalensis during Photobacterium damselae subsp. piscicida - Núñez Díaz, José Alberto; Fumanal, Milagros Elena; Mancera, Juan Miguel; Moriñigo-Gutiérrez, Miguel Ángel; Balebona-Accino, María del Carmen (My University, 2014)
The marine fish pathogen Photobacterium damselae subsp. piscicida (Phdp) is responsible for important outbreaks affecting several fish species including flatfish Solea senegalensis. The aim of this work was to identify the behavior of several target fish genes related with programmed cell death (apoptosis), iron metabolism mechanisms and immune system. After qPCR analysis IL-1β, IL6, NRAMP-1, C6, TGF-β1 and SQSTM1 gene expression was not detected in liver tissues. In addition, TF, UBQ, FERR-M, HSP90AA, HSP90AB and HSP70 did not change transcription levels compared to non infected soles. On the contrary, LYS-G, HP-1, TNF-α, TRAF-3, NCCRP1, HAMP-1, C7 and stress proteins GPx and GP96 were up-regulated 24h post-infection compared with the control group. Increased transcription of C3 gene was observed only 48h after infection, whereas HAMP-1, HP and C3 were down-regulated 48 or 72h post-infection.
Keywords: Peces - Microbiología; Solea; Photobacterium